2022
DOI: 10.1177/10556656221125377
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Peer Difficulties of Children with Cleft Lip and/or Palate: A Systematic Review and Meta-Analysis

Abstract: Objectives A systematic review and meta-analysis were conducted to determine if children born with cleft lip and/or palate are at increased risk of psychological and peer difficulties, and if so, which difficulties they develop. Methods EMBASE, MEDLINE, and PsycINFO were searched for English language studies published between January 2005 and January 2022 which investigated the psychological outcomes and peer function of children with nonsyndromic cleft lip and palate. Outcomes included internalizing problems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 71 publications
0
10
1
Order By: Relevance
“…Despite previous studies indicating minor differences in levels of well-being between groups based on age, gender and cleft visibility, 9,29,30 Mann-Whitney U tests did not reveal any within-group differences. This may be due to the small number of study participants.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…Despite previous studies indicating minor differences in levels of well-being between groups based on age, gender and cleft visibility, 9,29,30 Mann-Whitney U tests did not reveal any within-group differences. This may be due to the small number of study participants.…”
Section: Discussioncontrasting
confidence: 92%
“…A previous systematic review has indicated there is great variability in the incidence of psychological difficulties and well-being in children born with CL/P. 9 The current study suggests that children Institute and Victorian Infrastructure Operating Fund. We would also like to thank Ivy Hsieh for her assistance with data collection on this project.…”
Section: Con Clus Ionsmentioning
confidence: 58%
See 3 more Smart Citations